Transgenic Papaya: Can we Proceed beyond the Hawaiian Experience? - Gonsalves, D.
The story of the development, deregulation, and commercialization of the papaya ringspot virus (PRSV)resistant transgenic 'SunUp' and 'Rainbow' papayas for Hawaii is quite well known at least among plant virologist and knowledgeable people in the field of papaya. Thus, the story will be only briefly recapped to provide a background for analyzing the major factors that contributed to the timely and practical deployment of the transgenic papaya in Hawaii. Several important factors were: 1)starting the biotechnology research before PRSV became a large problem in Hawaii, 2)focusing on getting a practical result, 3)blend of expertise of the research team, 4)small but consistent support, and 5)the era in which the transgenic papaya was deregulated and commercialized. Since its commercial release in Hawaii in 1998, the transgenic papaya has occupied a major portion of Hawaii's papaya industry, and is commonly accepted among consumers in Hawaii. Starting in 1992, efforts to move transgenic papaya beyond Hawaii were started with collaborative efforts of our laboratory with scientists in Brazil, Venezuela, Jamaica, Thailand, Bangladesh, and east Africa. Other laboratories have also made great strides in the technical development of PRSV-resistant transgenic papaya. These projects have advanced very well technically, but they are still far from reaching the ultimate goal of deregulation and commercialization. Why is this? A personal assessment on the present situation and the future of moving beyond the Hawaiian experience will be given.
Keywords: TRANSGENIC PAPAYA; PAPAYA RINGSPOT VIRUS; PATHOGEN-DERIVED RESISTANCE; TRANSFER OF TECHNOLOGY